2011
DOI: 10.14214/sf.76
|View full text |Cite
|
Sign up to set email alerts
|

Gap-phase dynamics in the old-growth forest of Lom, Bosnia and Herzegovina

Abstract: We investigated forest canopy gaps in the mixed beech (Fagus sylvatica L.), silver fir (Abies alba Miller), and Norway spruce (Picea abies (L.) Karst.) old-growth forest of Lom in the Dinaric Mountains of Bosnia and Herzegovina. Gap size, age, gap fraction, gapmaker characteristics and the structure and composition of gapfillers were documented to investigate gap dynamics. The percentages of forest area in canopy and expanded gaps were 19% and 41%, respectively. The median canopy gap size was 77 m 2 , and rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
45
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 45 publications
4
45
0
1
Order By: Relevance
“…Gap size had little influence on regeneration density in Lom, which was also found in a companion 263 study (Bottero et al 2011). This finding is confirmed by other studies in southeastern European …”
supporting
confidence: 60%
“…Gap size had little influence on regeneration density in Lom, which was also found in a companion 263 study (Bottero et al 2011). This finding is confirmed by other studies in southeastern European …”
supporting
confidence: 60%
“…(Čermák & Grundmann 2006) and from Slovakia (Konôpka & Pajtík 2015). A high pressure on fir and factually the disposal of its natural regeneration by game browsing were described by Bottero et al (2011) in Bosna and Herzegovina, by Jaworski et al (2002) in the Western Carpathians or by Klopcic et al (2010) in Slovenia; the latter authors reported about unfenced firbeech stands, where great damage to fir recruits or even the total disposal of fir regeneration by browsing was observed. In relation to the high game pressure Vrška et al (2001) concluded that selected forest stands should be fenced to provide natural spontaneous development of the regeneration of spruce-fir-beech forests.…”
Section: Resultsmentioning
confidence: 96%
“…Documented climatic events, likely coupled with anthropogenic disturbances, are indicated in this study by the following: (1) beech dominance among small trees in all inventories and its increase overall dbh classes in recent inventories; (2) the future decrease of the beech middle-story modelled with transition probabilities; (3) the IQ shape of dbh frequency distribution in the 1950s for conifers in all old-growth forests and (4) changes in dbh frequency distributions. Other recent studies have also suggested these events, e.g., the disturbance study in Motta et al [47] and gap age analysis in Bottero et al [48].…”
Section: Historical Evidence and Possible Causes Of Beech Progressionmentioning
confidence: 83%
“…These forests therefore represent an excellent resource for the study of interactions of climatic fluctuations and indirect anthropogenic disturbances, both of which are well documented in the literature [33,[37][38][39][40][41]. The Janj old-growth forest has received less scientific attention [42,43] than the forests of Perucica (e.g., [5,19,[44][45][46]) and Lom [32,47,48]. The aims of this study were (1) to describe the structural changes over a 60-year period in the Janj old-growth forest and (2) to compare and contrast the changes with those in the Lom and Perucica (Bosnia and Herzegovina) old-growth forests and other similar old-growth forests in Europe.…”
mentioning
confidence: 99%